2021
DOI: 10.3390/ijms22031244
|View full text |Cite
|
Sign up to set email alerts
|

APOE: The New Frontier in the Development of a Therapeutic Target towards Precision Medicine in Late-Onset Alzheimer’s

Abstract: Alzheimer’s disease (AD) has a critical unmet medical need. The consensus around the amyloid cascade hypothesis has been guiding pre-clinical and clinical research to focus mainly on targeting beta-amyloid for treating AD. Nevertheless, the vast majority of the clinical trials have repeatedly failed, prompting the urgent need to refocus on other targets and shifting the paradigm of AD drug development towards precision medicine. One such emerging target is apolipoprotein E (APOE), identified nearly 30 years ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 98 publications
(134 reference statements)
1
23
0
Order By: Relevance
“…As pointed out above, one of the most notable things about CRISPR/Cas-based gene therapy is how rapidly it has evolved. But as exciting as this development, experts in fields ranging from science, medicine to bioethics, including our group, have cautioned that the progress in the clinical applications related to the technology, should not overtake the associated shortcomings related to research and ethical complications that arise ( Yang et al, 2021 ; Angrist et al, 2020 ; MacDougall et al, 2021 ). In fact, the ethical issues related to the CRISPR/Cas technology have made headlines most recently.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out above, one of the most notable things about CRISPR/Cas-based gene therapy is how rapidly it has evolved. But as exciting as this development, experts in fields ranging from science, medicine to bioethics, including our group, have cautioned that the progress in the clinical applications related to the technology, should not overtake the associated shortcomings related to research and ethical complications that arise ( Yang et al, 2021 ; Angrist et al, 2020 ; MacDougall et al, 2021 ). In fact, the ethical issues related to the CRISPR/Cas technology have made headlines most recently.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases have Mendelian inheritance trends, which often result in the early onset of symptoms through altered metabolism of Aβ, 7 but for most patients, the genetic predisposition is more complex. 8 The most common genetic risk factor is variants of the APOE gene, 9 which is believed to mainly increase the risk for AD through modulating the accumulation of Aβ. 10 In addition, genome-wide association studies (GWASs) have identified additional single-nucleotide polymorphisms (SNPs) with risk effects for AD dementia.…”
mentioning
confidence: 99%
“…Mechanistic insights gained from these studies may be harnessed to optimize treatment strategies for subjects with a high risk of cardiometabolic and neurological diseases due to APOE gene polymorphism. Several approaches, such as the use of apoE mimetic peptides [ 180 ], apoE4 structural correctors [ 179 ], modulators of apoE trafficking pathways [ 181 ], apoE antisense oligonucleotides [ 182 ] and APOE gene therapy [ 183 ] have been proposed and tested in preclinical models with various efficacies. The challenge of these approaches is the specific targeting to appropriate tissues and cell types, where their effectiveness can be optimized without any adverse effects.…”
Section: Conclusion and Perspectivementioning
confidence: 99%